2017
DOI: 10.4172/pharmaceutical-sciences.1000309
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Barriers and Facilitators of Clinical Practice Guidelines Implementation among Physicians

Abstract: Alnaim and Almazrou.: Barriers and Facilitators of Clinical Practice GuidelinesThere is a gap in understanding the barriers and facilitators related to guideline implementation in Saudi Arabia. A descriptive cross sectional study was conducted to identify the factors that may act as barriers or facilitators of clinical practice guidelines used by physicians working in Riyadh, Saudi Arabia. A survey was distributed to 215 physicians working at universities and government hospitals in Riyadh city. The survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Hemorheology is critical in evaluating the development and progression of diseases. Due to an increase in age, hyperviscosity emerges in response to the aging and decline in organs or tissues, which can induce the anomaly in the vascular morphology and hemorheology in the microenvironment, thus affecting the physiological function (Alnaim and Almaz, 2017, Eseyin et al, 2018, Gao et al, 2017, Godsland et al, 1998, Sorlie et al, 1999, Wang et al, 2018). A great number of experimental and clinical studies have conformed the interaction between the geriatric diseases and hyperviscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorheology is critical in evaluating the development and progression of diseases. Due to an increase in age, hyperviscosity emerges in response to the aging and decline in organs or tissues, which can induce the anomaly in the vascular morphology and hemorheology in the microenvironment, thus affecting the physiological function (Alnaim and Almaz, 2017, Eseyin et al, 2018, Gao et al, 2017, Godsland et al, 1998, Sorlie et al, 1999, Wang et al, 2018). A great number of experimental and clinical studies have conformed the interaction between the geriatric diseases and hyperviscosity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 98% had confidence in well-developed guidelines especially for the management of diabetic keto-acidosis [19]. Almazrou and Alnaim (2018), in Riyadh, Saudi Arabia, found that 89% of physicians used clinical guidelines in the management of their patients either because they were based on evidence (84%) or because it was a requirement by the institutions where they work (40%) [21]. The main barriers against the implementation of clinical guidelines in the region were the lack of awareness of the guideline and knowledge of its use and application [21].…”
Section: Introductionmentioning
confidence: 99%
“…Almazrou and Alnaim (2018), in Riyadh, Saudi Arabia, found that 89% of physicians used clinical guidelines in the management of their patients either because they were based on evidence (84%) or because it was a requirement by the institutions where they work (40%) [21]. The main barriers against the implementation of clinical guidelines in the region were the lack of awareness of the guideline and knowledge of its use and application [21]. Also, a self-administered questionnaire conducted in Riyadh found that 40% of physicians did not consider sleep disorders a distinct specialty [22].…”
Section: Introductionmentioning
confidence: 99%
“…1 ml of double distilled water to dissolve CAL-n 2 mg purified polysaccharide, formulated as a 2 mg/ml concentration of the polysaccharide solution was analyzed by liquid chromatography under the same conditions, record retention time, to obtain samples of the elution volume polysaccharides (Cetindag et al, 2019, Alnaim and Almaz, 2017), by formula obtained Kav, then Kav polysaccharide sample values into a standard curve obtained l g Mw, finally calculated molecular weight polysaccharide test sample (see Fig. 5).…”
Section: Methodsmentioning
confidence: 99%